PERBANDINGAN SISTEM HUKUM INDONESIA DENGAN INGGRIS TERKAIT PERLINDUNGAN DESAIN INDUSTRI TERHADAP PRODUK TEKSTIL - Chandra Pratama Sitorus; Elfrida Ratnawati (Ensiklopedia of Journal, 2023)
Industrial Design initially developed in the textile and handicraft sectors which were mass-produced in England. On march 23, 1883 a convention was held in Paris called the Paris Union or known as The Paris Convention for The Protection of Industrial Property, which became the first step in the formation of international provisions regarding industrial design, namaley arrangements ini Trade Related Aspects of Intellectual Property Rights (TRIPs). In indoensia, industrial design is something different from copyright. In the United Kingdom there are several forms of protection against industrial desigsn. Legal protection is to provide protection and aims to integrate and coordinate various interests in society. As one of the pioneers of industrial design protection, textiles are specifically regulated in the TRIPs agreement in which the state is given the freedom to provide protections or through copyright provisions because textile products are cobsidered to have a short life cysle.Keywords: Industrial Design, Design Protection, Testile.